2007
DOI: 10.1158/0008-5472.can-07-1089
|View full text |Cite
|
Sign up to set email alerts
|

Isoobtusilactone A Induces Cell Cycle Arrest and Apoptosis through Reactive Oxygen Species/Apoptosis Signal-Regulating Kinase 1 Signaling Pathway in Human Breast Cancer Cells

Abstract: This study is the first to investigate the anticancer effect of isoobtusilactone A (IOA) in two human breast cancer cell lines, MCF-7 and MDA-MB-231. IOA exhibited effective cell growth inhibition by inducing cancer cells to undergo G 2 -M phase arrest and apoptosis. Further investigation revealed that IOA's inhibition of cell growth was also evident in a nude mice model. Cell cycle blockade was associated with increased levels of p21 and reduced amounts of cyclin B1, cyclin A, cdc2, and cdc25C. IOA also enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(84 citation statements)
references
References 44 publications
2
81
0
1
Order By: Relevance
“…During the G 2 phase, cyclin B/cdc2 complex remains inactive by phosphorylation of cdc2 at Tyr15. Cdc25C, a phosphatase, is necessary for the G 2 -M transition that can remove the phosphate group of cdc2 at Tyr15 and then restore the function of cyclin B/cdc2 complex, resulting in M-phase entrance (18,23,25). By means of immunoblot data, we found that DHE causes cyclin D1 and cyclin D2 degradation.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…During the G 2 phase, cyclin B/cdc2 complex remains inactive by phosphorylation of cdc2 at Tyr15. Cdc25C, a phosphatase, is necessary for the G 2 -M transition that can remove the phosphate group of cdc2 at Tyr15 and then restore the function of cyclin B/cdc2 complex, resulting in M-phase entrance (18,23,25). By means of immunoblot data, we found that DHE causes cyclin D1 and cyclin D2 degradation.…”
Section: Discussionmentioning
confidence: 85%
“…Cell Proliferation and Clonogenic Assays Cells were plated in 96-well culture plates (1 × 10 4 per well) and treated with vehicle alone (0.1% DMSO) and various concentrations of DHE for 48 h. Inhibition of cell proliferation was measured by 2,3-bis[2-methoxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide inner salt (XTT) assay as described previously (18). To determine long-term effects, cells (1,000 per well) were treated with DHE at various concentrations for 3 h. After being rinsed with fresh medium, cells were allowed to form colonies for 14 d and then were stained with crystal violet (0.4 g/L; Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The release of serum-starved HEK 293 cells into S phase or cell cycle arrest at the G 2 /M phase in MCF-7 (human breast adenocarcinoma) cells enhanced ASK1 activity without affecting ASK1 protein expression level. 21,34 In order to investigate how ASK1 is regulated during mitosis, we used nocodazole, an antineoplastic agent that interferes with microtubule polymerization, to synchronize cells in prometaphase of mitosis. Both MCF-7 and HEK 293 cells were successfully synchronized in mitosis after 16 h of nocodazole treatment ( Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Although ASK1 phosphorylation is known to be involved in the regulation of apoptosis, only a few reports show that ASK1 phosphorylation or activity is dependent on the cell cycle. 21,34 In this study, we examined the functional relationship between Cdc25C and ASK1 and identified a novel function of Cdc25C phosphatase that can dephosphorylate and inhibit ASK1 in interphase but not in mitosis. Furthermore, we demonstrated that Cdc25C phosphorylation status plays a critical role in the interaction with and the activity of ASK1.…”
mentioning
confidence: 99%